Aluminium-carbon nanotubes composites produced from friction stir processing and selective laser melting - Du, Zhenglin (2017)
Aluminium reinforced with multi-wall carbon nanotubes was produced using friction stir processing and selective laser melting. Very fine grains were successfully achieved in both methods with high Vickers hardness values. Cavities were present in selective laser melting of AlSi10Mg reinforced with multi-wall carbon nanotubes parts resulting in higher stress concentration brittle fracture appearance. The high laser absorption and higher thermal conductivity of multi-wall carbon nanotubes resulted in the formation of the cavities in the melted parts. However, the fractography images showed dimpled like appearance indicating a ductile fracture mechanism. Multi-wall carbon nanotubes were observed at the fracture sites indicating the presence of a crack-bridging mechanism. In comparison to carbon nanotubes reinforced aluminium by friction stir processing, selective laser melting produces aluminium reinforced aluminium with better mechanical properties.